ChemInform Abstract: A Photochemical Route to Benzo[a]carbazoles via Domino Elimination/Electrocyclization of 2‐Aryl‐3‐(1‐tosylalkyl)indoles. Issue 32 (18th July 2013) - Protti, Stefano; Palmieri, Alessandro; Petrini, Marino; Fagnoni, Maurizio; Ballini, Roberto; Albini, Angelo
Abstract The reaction can also be conducted in THF.